Assisting Decision-Making on Age of Neutering for Mixed Breed Dogs of Five Weight Categories: Associated Joint Disorders and Cancers - Hart, Benjamin L.; Hart, Lynette A.; Thigpen, Abigail P.; Willits, Neil H. (Frontiers in Veterinary Science, 2020)
The early neutering of male and female dogs and its relationship to an increased risk of joint disorders and some cancers has recently become a concern, raising questions about the standard practice in the U.S. and much of Europe of neutering by 6 months of age. A noteworthy recent finding from this center is that there are major breed differences with small dog breeds generally showing little vulnerability compared with breeds with larger body size. These findings on purebreds raise questions for dog owners and veterinarians about mixed-breed dogs since they outnumber purebreds as household pets. The purpose of this study was to examine a sample of mixed breed dogs of five weight categories using the same veterinary hospital database and diagnostic criteria for joint disorders and cancers as used in the published papers on the Golden Retriever, Labrador Retriever, German Shepherd Dog. The joint disorders examined were hip dysplasia, cranial cruciate ligament tear or rupture, and elbow dysplasia. The cancers were lymphoma, mast cell tumor, hemangiosarcoma, and osteosarcoma. For the dogs in weight categories less than 20 kg, no increased risks were found for these joint disorders and cancers. This means that caregivers with these lighter weight dogs can choose a neutering age with no concern of elevating the dog's risks for these diseases. Regarding cancers, there was no significant increased occurrence of one or more cancers that were followed compared with intact dogs in any weight category. However, in the three categories of dogs weighing at least 20 kg, neutering before 1 year generally was significantly associated with risks of one or more joint disorders above that of dogs left intact. This information can be useful to dog caregivers in deciding on the age at which to neuter specific dogs, and for veterinarians offering guidance to pet owners.